The Development of Concepts in the Wujūdiyya Teachings - Miswari, Miswari (ADDIN, 2023)
This article aims to analyze the development of philosophical Sufism of the Wahdat al-Wujūd school or in Malay-Nusantara term called Wujūdiyya. The research approach uses descriptive analysis. The research data use references related to the Wahdat al-Wujūd study. The research findings show that the essence of Sufism is philosophical Sufism. In the early days, philosophical Sufism focused on the philosophical meaning of some verses of Al-Qur’an. The early generations of philosophical Sufism were taught, among others, by Rabi’ah al-Adawiyah and Sufyān ats-Tsaurī. The philosophical study of Sufism was started by Dhu’nūn al-Misrī. Then followed by Abū Yazid al-Bistamī with Hulūl teachings and Abū Mansūr al-Hallaj with Ittihad teachings. The teachings of Hulūl and Ittihad were then questioned by ‘Ain al-Qudhad Hamadanī, because these concepts necessitate duality, even though Wahdat al-Wujūd does not accept dual existence. ‘Urafā at that time did not have adequate language tools to teach Wahdat al-Wujūd. It was only at the time of Ibn ‘Arabī that Wahdat al-Wujūd could be explained systematically and holistically, because at the time of Ibn ‘Arabī, philosophical language was very mature thanks to al-Hikmah al-Masya’iyyah, especially by Ibn Sīnā.